Induced anisotropic superconductivity in ionic liquid cation intercalated 1T-SnSe2. (27th November 2020) - Rousuli, Awabaikeli; Zhang, Haoxiong; Zhang, Kenan; Zhong, Haoyuan; Feng, Runfa; Wu, Yang; Yu, Pu; Zhou, Shuyun
Abstract: The weak van der Waals interaction between adjacent layers of quasi-two-dimensional materials provides opportunities for inserting intercalants to induce novel properties distinct from the host materials. Here we report induced superconductivity in an intercalated SnSe2 crystal by using a new type of intercalants—organic cations from ionic liquids, [C2 MIm] + and [DEMB] + . The intercalation of both cations increases the interlayer spacing and leads to induced superconductivity with T c of 7.1 and 6.9 K and a large superconducting anisotropy. Angle-resolved photoemission spectroscopy and Hall measurements reveal the importance of electron doping by the cations in the induced superconductivity, and the interlayer expansion and electric polarization of the cations in the large anisotropy. Our work reports induced superconductivity in an intercalated material with new intercalants which contribute both charge carriers and interlayer expansion, and provides a new pathway to the manipulation of superconductivity in layered materials.